Dynamic mechanical analysis of polyethylene terephthalate/hydroxyapatite biocomposites for tissue engineering applications - S.A.P. Sughanthy; M.N.M. Ansari; A. Atiqah (Journal of Materials Research and Technology, 2020)
Synthetic biomaterials are widely used for the treatment of diseased or damaged tissue in the field of tissue engineering. Polyethylene terephthalate (PET) is a synthetic thermoplastic engineering polymer with high commercial and industrial interest and has been widely used as implant material in biomedical engineering. Despite that, PET has limited applications due to its high hydrophobicity. Hydroxyapatite (HA) is one of the known biocompatible ceramic for the development of porous scaffolds for bone replacement and tissue engineering due to its resemblance to the mineral constituents of human bones and teeth. Therefore, HA was functionalized into the PET matrix in order to improve the limitation. In this research, PET-HA nano-biocomposite scaffold was electrospun using the electrospinning system. PET and HA were dissolved using trifluoroacetic acid (TFA) and dichloromethane (DCM). The nanofibrous scaffolds were produced at optimum process parameters. The morphology studies were performed using a Scanning Electron Microscope (SEM) and thermomechanical properties were evaluated using Dynamic Mechanical Analysis (DMA). From the morphology analysis, PET-HA nano-biocomposite scaffold which composed of 96% of PET and 4% of HA, has obtained the largest fiber diameter. The DMA analysis showed that the addition of HA improved mechanical properties. However, PET-HA nano-biocomposite scaffold composed of 98% of PET and 2% of HA was preferred as it has the lower value of storage and loss modulus because the application was focusing on the skin where the more flexible scaffold was needed. The PET-HA nano-biocomposite scaffold fabricated has good potential to be used in tissue engineering applications. Keywords: Biomaterials, Polyethylene terephthalate (PET), Hydroxyapatite (HA), Dynamic mechanical analysis (DMA), Tissue engineering